Write and Move Learning Model Based on Digital Literacy - Indra Suhendra; Rahman; Lina Marlina Nur Rizkiya (International Conference on Elementary Education, 2023)
The culture of literacy in Indonesia is very low. Reading and writing had not been made a necessity in daily life. People had not been accustomed early to love reading and writing. The problem of digital literacy then appears and becomes a new problem when the problem of language literacy was unfinished in Indonesia which demands to all to be able to utilize and minimize all negative impacts of technology itself. In this article, researchers used research studies which explained about alternative of the problem-solving that was experienced by teachers and students by explaining about the write and move models that were modifications of the cooperatives learning model, writing processes and computer media. The write and move learning model can motivate students and teachers to continuously develop their language and digital literacy skills.